Rhizosphere bacterial communities of dominant steppe plants shift in response to a gradient of simulated nitrogen deposition - Yang, An; Liu, Nana; Tian, Qiuying; Bai, Wenming; Williams, Mark; Wang, Qibing; Li, Linghao; Zhang, Wen-Hao (Frontiers in Microbiology, 2015)
We evaluated effects of 9-year simulation of simulated nitrogen (N) deposition on microbial composition and diversity in the rhizosphere of two dominant temperate grassland species: grass Stipa krylovii and forb Artemisia frigida. Microbiomes in S. krylovii and A.frigida rhizosphere differed, but changed consistently along the N gradient. These changes were correlated to N-induced shifts to plant community. Hence, as plant biomass changed, so did bacterial rhizosphere communities, a result consistent with the role that N fertilizer has been shown to play in altering plant-microbial mutualisms. A total of 23 bacterial phyla were detected in the two rhizospheric soils by pyrosequencing, with Proteobacteria, Acidobacteria and Bacteroidetes dominating the sequences of all samples. Bacterioidetes and Proteobacteria tended to increase, while Acidobacteria declined with increase in N addition rates. TM7 increased >5-fold in the high N addition rates, especially in S. krylovii rhizosphere. Nitrogen addition also decreased diversity of OTUs (operational taxonomic units), Shannon and Chao1 indices of rhizospheric microbes regardless of plant species. These results suggest that there were both similar but also specific changes in microbial communities of temperate steppes due to N deposition.